Анализ расчетных методов оценки работоспособности элементов автомобильных шин - Ларин, А. Н.; Коханенко, В. Б.; Конохов, Владимир Иванович; Школьный, С. М. (НТУ "ХПИ", 2006)
Decided of problems of fatigue and type of failure for tires there are large complex in connections of many aspects. The contemporary systems of finite element analysis allow to obtained of solutions for the several moments of this total problem
Keywords: пневматические шины; колесо; деформация; токопроводящая резина